TRANSFORMATION OF RUSSIAN CASPIAN PASTURE ECOSYSTEMS UNDER THE NEW SOCIO-ECONOMIC CONDITIONS - V. G. Lazareva; V. A. Bananova; K. M. Petrov; D. A. Boldyreva; G. M. Borlikov (Юг России: экология, развитие)
The aim of this work is to study the modern vegetation of the Russian Caspian Sea region. On its basis we identified the trend of pasture degradation under the new socio-economic conditions. Materials andMethodology. The article presents statistical data on the dynamics of livestock in arid, humid and contemporary, transitional climatic cycles. The first (1987) cycle is characterized by the highest, the second (1995) by the lowest and third (2014) by increasing load of cattle pasture. Furthermore, these periods have coincided with the change of political situation in the country. The study of key areas of vegetation pastures was carried out according to the "Field geobotany" guideline (1974) by expeditionary and stationary methods.Results. Years of research have allowed following the dynamics of pasture conditions for faulty stages in different types of vegetation to determine the modern state under the influence of modern grazing pressure. It was found that the indicators of pasture digression are species composition as well as other derivatives of plant communities. In the steppe cenoses the weak stage is indicated by caespitosa cereals, the average – domination of xerophilic semishrubs, very strong - ephemera, ephemeroids, harmful and poisonous plants. In the zonal suffrutescent deserts degradation becomes clearly apparent in the severe stages of failure. According to the degree of failure layering, complexity and productivity of plant communities are reduced.Conclusion. Currently, as a result of the increasing livestock population, the northern part of the Caspian (Sarpinskaya lowlands), is characterized by moderate and severe stages of desertification. In the next five years, the region can once again become a zone of ecological disaster as in the late 80s of the twentieth century.